Intolerant Indian - "Adhikari, Gautam" (New Delhi, 2011)
It's dangerous to play around with the idea of India, but a new breed of intolerant Indians is doing just that Far too many Indians today do not seem to appreciate the idea of pluralist tolerance, which forms the structural framework of Indian democracy. They see pluralism as phony and tolerant secularism as hypocritical or irrelevant to an existence centered on narrow religious, regional or ethnic identities. Extremist religious ideologies as well as violent politics of mindless forces on the right and the left have often overshadowed the idea of a tolerant society that our founding fathers dreamed of, where many views would compete for public attention and where the motto 'live and let live' would be the nation's guiding philosophy. This essay is a plea for the restoration of reason in public life. It is written from the point of view of a liberal-secular democrat, who also happens to be an agnostic.
Keywords: Politics-India